Parting shot ebook - Barclay, Linwood (2017)
From  New York Times  and #1 international bestselling author Linwood Barclay comes a new, standalone blockbuster thriller that spins off from the events of the explosive Promise Falls trilogy. If you made a mistake that took someone's life, you'd remember it . . . wouldn't you?      After a tragedy rocks the community of Promise Falls, Cal Weaver is asked to investigate the threats being made to the accused's family. He's heard all about it on the news: the young man who drank too much, stole a Porsche and killed a girl, and who claimed afterwards not to remember a single thing. The whole town is outraged that he got off lightly, but for reasons Cal can't explain, he accepts the job. Then Cal finds himself caught up in a vicious revenge plot, chasing someone set on delivering retribution. In Cal's experience, it's only ever a matter of time before threats turn into action. . . .      A gripping thriller packed with scandal, from the master of the twist you never saw coming.